Increasing Productive Teacher Pedgogic Competence through Academic Supervision of Technical Staff Meeting at SMK Negeri 1 Kutalimbaru - Saut Purba; Abdul Hasan; Keysar Panjaitan; Binsar Maruli Tua Pakpahan (Budapest International Research and Critics University, 2023)
This study aims to determine the application of staff meeting technical academic supervision to improve the pedagogical competence of productive teachers at SMK Negeri 1 Kutalimbaru. The competence of productive teachers at SMK Negeri 1 Kutalimbaru can be increased. The subjects of this study were twenty-four productive teachers. The research instrument used to determine teacher competency was a pedagogic competency test (Ministry of Education and Culture (2017)), observation sheets, interviews and questionnaires. The research method used was action research school. The research implementation consisted of two cycles. Each cycle consists of four stages of activity, namely: planning, implementing, observing and reflecting.85.43%with the Good category and cycle II achieved an average value of91.85%with the Very Good category. The implications of this study indicate that the application of academic supervision of staff meeting techniques can increase the competence of productive teachers in developing pedagogical competence at SMK Negeri 1 Kutalimbaru.